2010
DOI: 10.1007/s11747-010-0211-8
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of sales performance: a contemporary meta-analysis. Have salespeople become knowledge brokers?

Abstract: It has been 25 years since the publication of a comprehensive review of the full spectrum of salesperformance drivers. This study takes stock of the contemporary field and synthesizes empirical evidence from the period . The authors revise the classification scheme for sales performance determinants devised by Walker et al. (1977) and estimate both the predictive validity of its sub-categories and the impact of a range of moderators on determinant-sales performance relationships. Based on multivariate causal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
423
0
23

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(509 citation statements)
references
References 111 publications
(146 reference statements)
26
423
0
23
Order By: Relevance
“…Ao atuar na área de serviços, o funcionário tem acesso às informações dos clientes disponíveis na organização, facilitando o entendimento das suas necessidades e experiências (Yu et al, 2013). Com as informações em mente, a venda tende a ser adaptativa e orientada ao cliente, oferecendo produtos que sejam congruentes com sua necessidade (Verbeke, Dietz, & Verwaal, 2011). Em outras palavras, ao fazer a adaptação às demandas do cliente, o funcionário cria valor via informação, tornando-se um forte direcionador do volume de vendas por meio do aumento na intenção de compra do cliente (Homburg, Müller, & Klarmann, 2011).…”
Section: Efeito Do Comportamento Ambidestro No Desempenhounclassified
See 1 more Smart Citation
“…Ao atuar na área de serviços, o funcionário tem acesso às informações dos clientes disponíveis na organização, facilitando o entendimento das suas necessidades e experiências (Yu et al, 2013). Com as informações em mente, a venda tende a ser adaptativa e orientada ao cliente, oferecendo produtos que sejam congruentes com sua necessidade (Verbeke, Dietz, & Verwaal, 2011). Em outras palavras, ao fazer a adaptação às demandas do cliente, o funcionário cria valor via informação, tornando-se um forte direcionador do volume de vendas por meio do aumento na intenção de compra do cliente (Homburg, Müller, & Klarmann, 2011).…”
Section: Efeito Do Comportamento Ambidestro No Desempenhounclassified
“…Como proposto pela teoria da ambidestria (Gibson & Birkinshaw, 2004), o balanceamento entre as atividades simultâneas conduz ao sucesso nos resultados, em detrimento do foco demasiado em apenas um grupo de atividades, o que pode levar a um estado de desequilíbrio e prejudicar o desempenho (March, 1991). Ao manter altos níveis de dedicação nas atividades simultâneas de provisão de serviços e de cross-/up-selling (Junni et al, 2013), é possível, ao funcionário de linha de frente, oferecer um suporte mais orientado ao cliente (Verbeke et al, 2011) e gerar um maior grau de satisfação (Yu et al, 2015) e de comportamento recíproco no cliente (Homburg et al, 2011).…”
Section: Considerações Teóricasunclassified
“…Na medida em que os vendedores adquirem experiência, passam a desenvolver maior maturidade profissional, que é importante para as vendas e as tarefas (Stan, Evans, Arnold, & McAmis, 2012 (Stan et al, 2012) e adaptação à necessidade do cliente (Cron & Slocum, 1986;Rapp, Ahearne, Mathieum, & Schillewaert, 2006). A experiência propicia aos vendedores uma bagagem mais adequada para práticas de vendas, como o desenvolvimento de adaptabilidade na abordagem de vendas (Verbeke et al, 2011) e a orientação para o cliente (Franke & Park, 2006). É importante distinguir a experiência em vendas geral da experiência em vendas na empresa.…”
Section: Experiência Do Vendedorunclassified
“…Churchill et al (1985) suggested that organizational variables are related with salesperson performance and (Verbeke et al, 2011) reported that internally located salespeople are vulnerable to organizational variables. Because of their powerful influence, internal organizational variables are a necessary component of any proposed model of retail employee sales performance which are directly controllable at the store level.…”
Section: Job Characteristicsmentioning
confidence: 99%
“…As a result, the experience of retail salespersons are increased level of role uncertainty. According to role uncertainty which is acknowledged to be a significant and constant part of the sales environment (Babin and Boles, 1996) and it is strongly and consistently related with reduced salesperson (Verbeke et al, 2011) and retail employee sales performance (Arnold et al, 2009) therefore must be accounted for in any attempt to model retail employee sales performance. Singh (1993) claimed that observing role uncertainty as a uni-dimensional construct "Ignored the conceptual thesis" provided by Kahn et al (1964) when they introduced the construct to organizational research and that studies do not explain a significant amount of the variance in employee job outcomes.…”
Section: Job Characteristicsmentioning
confidence: 99%